Semi-Synthesis of Marine-Derived Ilamycin F Derivatives and Their Antitubercular Activities - Li, Jun; Liu, Zhiyong; Hong, Mingye; Sun, Changli; Zhang, Tianyu; Zhang, Hua; Ju, Jianhua; Ma, Junying (Frontiers in Chemistry, 2021)
Tuberculosis (TB) is still a global disease threatening people’s lives. With the emergence of multi-drug-resistant Mycobacterium tuberculosis the prevention and control of tuberculosis faces new challenges, and the burden of tuberculosis treatment is increasing among the world. Ilamycins are novel cyclopeptides with potent anti-TB activities, which have a unique target protein against M. tuberculosis and drug-resistant strains. Herein, ilamycin F, a major secondary metabolite isolated from the marine-derived mutant strain Streptomyces atratus SCSIO ZH16 ΔilaR, is used as a scaffold to semi-synthesize eighteen new ilamycin derivatives (ilamycin NJL1–NJL18, 1–18). Our study reveals that four of ilamycin NJLs (1, 6, 8, and 10) have slightly stronger anti-TB activities against Mtb H37Rv (minimum inhibitory concentration, 1.6–1.7 μM) compared with that of ilamycin F on day 14th, but obviously display more potent activities than ilamycin F on day 3rd, indicating anti-TB activities of these derivatives with fast-onset effect. In addition, cytotoxic assays show most ilamycin NJLs with low cytotoxicity except ilamycin NJL1 (1). These findings will promote the further exploration of structure-activity relationships for ilamycins and the development of anti-TB drugs.